A new genus of scuttle fly (diptera: phoridae) from Malaysia - Raja Muhammad Zuha Raja Kamal Bashah; Disney, R. Henry L. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Imparphora gen. nov., a new genus of scuttle fly is described from Malaysia. The Imparphora pahangensis sp. nov. is the type species of the new genus. A total of six mature females species and a male were collected from baited traps along UKM’s Trail at Fraser’s Hill Research Centre, Pahang. These findings expand the species diversity of scuttle flies in Malaysia especially in the highland forest. The comparisons with the nearest genera were explained herein.